Karakter Morfologi dan Morfometrik Lebah Sosial (Aphidae) di Pertanian Organik BEEMA HONEY Bogor - Mega Sumayana Purba; Jacobus S.A. Lamerkabel; John Alfred Patty (Fakultas Pertanian, Universitas Pattimura, 2023)
Indonesia has a biodiversity of flora both from forest and agriculture that can be used as a source of bee feed. The study aims to describe the morphological and morphometric characteristics of stinged and stingless honeybees in the BEEMA Honey organic farming environment in September-December 2022. The species of stinged bees and stingless bees found to belong to the genera Apis, Tetragonula, and Heterotrigona with species Apis cerana, Tetragonula sapiens, Tetragonula biroi, Tetragonula laeviseps, Tetragonula fuscobalteata, and Heterotrigona itama. The honey bee species are found in four locations: pollinator garden, Limasan garden house, in front of the plantation house, and below the water tank. Observations of morphological characters include body color, caput, thorax, and abdomen, while morphometric characters of bees include: A. cerana; The color of the abdomen is brownish-yellow with a body length of 14.03-15.00 mm. T. sapiens; The abdomen is colored and measures 4.34-4.55 mm in length. The abdomen and tergites one to six are black. T. biroi; The color of the abdomen is black and the length of the body is 2.75-3.25 mm. T. laeviceps is black and body length is 3.0-3.2 mm. T. fuscobalteata is blackish-brown and body length is 2.33-.2.70 mm. H. itama has a dark black body with a body length of 10.66-12.25 mm.